Spirituality as a protective factor against suicide in Medical students (Research, Society and Development, 2025)
Introduction: Suicide is a major global public health issue and the fourth leading cause of death among young people aged 15 to 29 in Brazil. Medical students show twice the risk of suicidal ideation compared to the general population, due to academic overload, social pressure, sleep deprivation, and higher rates of mental disorders. In this context, spirituality emerges as a possible protective factor. Objective: To investigate spirituality among medical students as a potential protective factor against suicide. Method: Observational and descriptive literature review based on scientific articles, systematic reviews, and meta-analyses from databases such as PubMed and CAPES, addressing the relationship between spirituality and suicide prevention among medical students. Results: A high prevalence of psychological distress was observed, with suicidal ideation around 27.7% and suicide planning up to 12.5%. Risk factors included living alone (OR = 2.01), low socioeconomic status (OR = 2.43), and a history of mental disorders (OR = 3.12). Conversely, spirituality showed a protective effect, fostering resilience, adaptation, social support, and sense of purpose, and was associated with lower rates of depression, anxiety, and suicidal behavior. Conclusion: Medical students present high levels of psychological distress and suicide risk. When experienced positively, spirituality may act as a protective factor, promoting healthier coping and greater hope. It should be integrated with psychological and institutional prevention strategies for mental health care.